Market Access and Agricultural Diversification: An Analysis of Brazilian Municipalities - Bruno Benzaquen Perosa; Ramon Felipe Bicudo da Silva; Mateus Batistella (Land, 2024)
Market access has a deep impact on farmers’ decisions, influencing their choice of crops and technology adoption. Crop diversification depends on the availability of markets to trade the agricultural portfolio. This study explored how market access impacted the level of diversification in 5565 Brazilian municipalities from 2013 to 2021. We developed a regression model considering how variables related to market access and commercialization (storage, roads, distribution centers, commercialization credit, among others) affected a local (municipality level) diversification index. After environmental variables were controlled, the results indicated that most of the market access variables have a significant impact on diversification. We also used map analysis to analyze the regional patterns of specialization in Brazilian agriculture, concluding that logistics and commercialization infrastructure have strong influence on the level of diversification in Brazil, a major agricultural powerhouse in the world. The results indicate that market access variables affect diversification and should be considered by policy makers aiming to increase sustainability in agriculture and livestock.